THE EFFECT OF COOPERATIVE LANGUAGE LEARNING AND PERSONALITY TYPES TOWARDS ESSAY WRITING - Bejo Sutrisno; Yumna Rasyid; Aceng Rahmat (English Review: Journal of English Education, 2018)
This study is aimed to find out the effect of Cooperative learning techniques and personality types on English essay writing skill. This study was conducted at STIBA – IEC Jakarta for the fourth semester in the academic year 2016/2017. It was an experimental study with the factorial design 2 x 2 at 0.05 significance level. The sample was 32 students and divided into two groups which each group was 16 students. The research reveals that: (1) students’ English essay writing skill taught with Think-Pair-Share (TPS) technique was  higher than with Student Team Achievement Division (STAD) technique; (2) English essay writing skill on introvert personality type was higher than extrovert personality types; (3) there was interaction effect between learning techniques and personality type toward English essay writing skill; and (4) students with introvert type taught with TPS technique was higher than those taught with STAD technique. There is an interaction effect between learning techniques and personality types on English essay writing skills. Keywords: cooperative learning, essay writing skill, learning technique, personality type